1998
DOI: 10.1095/biolreprod58.4.911
|View full text |Cite
|
Sign up to set email alerts
|

Uterine Environment and Breed Effects on Erythropoiesis and Liver Protein Secretion in Late Embryonic and Early Fetal Swine1

Abstract: In this study we investigated erythropoiesis and fetal liver protein secretion during late embryonic (Day 24 and Day 30) and early fetal (Day 40) development in pigs from domestic white crossbred (WC) gilts with a normal (intact; INT) or crowded (unilateral hysterectomized/ovariectomized; UHO) uterine environment, or from prolific Chinese Meishan (MS) gilts. Increased fetal weight, fetal liver weight, placental weight, total red blood cells, hematocrit, blood hemoglobin content, and maternal plasma erythropoie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
50
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(58 citation statements)
references
References 41 publications
7
50
1
Order By: Relevance
“…fluid coincides with the time when fetal erythropoiesis is being initiated in the liver [6,21,22]. It also coincides with the critical period for fetal loss in the crowded uterus, which occurs around Day 40 of pregnancy [22,23].…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…fluid coincides with the time when fetal erythropoiesis is being initiated in the liver [6,21,22]. It also coincides with the critical period for fetal loss in the crowded uterus, which occurs around Day 40 of pregnancy [22,23].…”
Section: Discussionmentioning
confidence: 54%
“…By contrast, the affinity is the lowest between Days 50 to 70 and increases thereafter. Increased placental folate binding up to Day 50 of pregnancy may be needed to meet the requirement of the developing conceptus as fetal erythropoiesis is being initiated in the liver around Day 30 and reaches a maximum by Day 50 [6,21,22,25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A day 24-40 of gestation is a critical time progression for fetal erythropoiesis in pigs as well as survival in a crowded uterine environment. The uterine environment had little overall effect on erythropoiesis in white crossbreed pigs but did affect fetal survival, and crowding may compromise erythropoiesis in small fetuses (Pearson et al, 1998). Selection for increased ovulation rate has been very successful.…”
Section: Fth Polymorphisms Discovery and Associationmentioning
confidence: 99%
“…Indeed, the total vitamin B 12 concentration in uterine horns at 15 d of gestation represents between 180 and 300% of the total concentration in plasma, with the total volume of plasma being estimated at 4% of body weight (Matte . The physiological mechanism underlying this transfer is not well understood in pigs although one of the known B 12 carriers, transcobalamin I, has been identified in porcine endometrial tissues (Pearson et al 1998). Moreover, Guay et al (2002b) showed that a dietary supplement of 160 ppb similar to that used by Frederick and Brisson (1961) could be an efficient way to increase B 12 status as measured by the variation of plasma B 12 in early gestation (up to day 15).…”
Section: The Case Of Vitamin B 12mentioning
confidence: 99%